Applied Boron Increases Alfalfa Petiole Boron Concentration across Water Regimes, Not Yield. (1st November 2019) - Sapkota, Anish; Meccage, Emily; Stougaard, Robert N.; Bicego, Breno; Torrion, Jessica A.
Abstract : Boron (B) fertilization based on soil B status may prevent negative effects on alfalfa ( Medicago sativa L.) yield and quality. Our objective was to determine the effects of foliar‐applied B and water regimes on alfalfa yield and quality. A 2‐yr (2016–2017) study was done at Creston, MT in a fine sandy loam soil that tested 0.2 mg kg −1 B. Alfalfa was planted in 2016. Levels of B ranging from 0 to 2.24 kg B ha −1 were applied in association with three water regimes including rainfed, 50%, and 100% evapotranspiration (ET). There was no effect of B on yield or crude protein ( P > 0.05) in either year. Both B fertilization and irrigation application increased petiole B concentration. In 2017, the water regime × B level interaction was significant specifically for the yield of the second cutting ( P = 0.02), as well as for the relative feed value, neutral detergent fiber, and petiole B concentration in the third cutting ( P < 0.05). Irrigation decreased ( P < 0.01) forage quality only in the second cutting of 2016. Irrigation increased alfalfa yield by 45% in the establishment year (2016), but only by 12% in the following year. However, there was no yield difference observed ( P > 0.05) between the 100ET and 50ET treatments each year, and irrigation water productivity decreased in the second year of alfalfa growth. The foliar application of B on a B‐deficient soil did not increase yield or crude protein content of alfalfa, regardless of soil moisture availability. Core Ideas Application of B or irrigation increase petiole B concentration of alfalfa. Increases of petiole B due to B fertilization did not increase alfalfa yield and crude protein. Deficit irrigation did not reduce yield in alfalfa. Regardless of water regime, application of B on B‐deficient soil did not improve yield and crude protein of alfalfa.